Analisis Pendapatan Usaha Jamur Tiram Crispy - Ginting, Nina Maksimiliana (MuJAgri: Musamus Journal of Agribusiness, 2019)
Crispy oyster mushroom agroindustry is now much appreciated by the public, especially the community. Crispy oyster mushroom agroindustry is a new business, but seen from the prospect, chrispy mushroom is very wide open because although it is a new business, many consumers like it because chrispy mushroom which is a kind of fried food is healthier because it contains nutrients from organic oyster mushrooms. This study aims to see how much chrispy mushroom income and business feasibility of chrispy mushrooms. The determination of the research area was carried out purposively. The method used to determine the sample is the snowball sampling method. Data collected in this study consisted of primary data and secondary data. Data analysis method is done by calculating business income with R / C ratio (Return Cost Ratio). The income was Rp 2,562,593.14 with an average income of Rp 160,162.07 per 1 time of production. R / C Ratio is obtained at 1.82, which means the business is feasible. Keywords: mushroom; oyster; crispy; income; agroindustry